Analysis of Biology Learning Problems in Urban Schools and Their Solutions - Mulia, Azzahra; Wizali, Gesti Defani; Tirta, Keny Haliza; Suryanda, Ade; Lesmono, Edi (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2023)
The achievement of learning objectives can be disrupted because of issues that occur in learning so that learning activities cannot be carried out optimally. As a result, it is important to identify the issues arising in order to select the most suitable solution to resolve them. The study aimed to identify problems with learning urban biology at one of the senior high schools in Jakarta and to find answers to those problems. The research method is using a case study method; a type of research that involves an in-depth examination of one individual, a group, an organization, and so on over a set period of time. The study's data collection methods included observation and interviewing. The study's findings reveal the following issues in learning biology at one of the senior high schools in Jakarta: 1) The biology program's implementation on practical indicators, 2) The redesigned 2013 curriculum, which is considered inconvenient for students and teachers to use, 3) Learning media selection and 4) Student learning interest. The solution to the problems of learning biology at senior high school in Jakarta is to understand the concept of implementing the 2013 curriculum so that it can provide innovative learning methods, can optimize the learning media that are being used, and understand the cognitive development of students with good communication skills.